PENANGANAN PERKARA TINDAK PIDANA KORUPSI OLEH KEJAKSAAN NEGERI KUALA SIMPANG SETELAH DIBENTUKNYA PENGADILAN TINDAK PIDANA KORUPSI DI DAERAH - Choirun Parapat; Madiasa Ablisar; Marlina Marlina; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT Legislation, which regulates the authority of prosecutors in prosecuting tipikor cases, does not give full authority to prosecutors as the only prosecuting institution although KPK (Corruption Eradication Committee) also has the authority to prosecute tipikor cases. The implementation of handling tipikor cases after the establishment of Tipikor Court of Justice, Banda Aceh, has the implication on the slowness of the bureaucratic process in the District Court, Kuala Simpang, for obtaining the license of arresting, confiscating, searching, and detaining; besides that, it is costly. Progressive efforts made are as follows: budget is increased, hearing schedule is united, some witnesses’ testimony is read before in the hearing, the cases are handled by the same judges, witnesses are examined simultaneously, the number of prosecutors is reduced, and returning the loss of the State is relatively small. It is recommended that the District Attorney’s Office carry out their authority in prosecuting tipikor cases neutral and unbiased. The government should establish Tipikor Court of Justice in every District/Town, and progressive efforts should be focused on the increase in budget. Keywords :     Tipikor, Tipikor Court of Justice, Prosecution, Progressive, District Attorney’s Office, Kuala Simpang